Encephalothoracic trauma - Benedek, Pedro (Cirugía del Uruguay, 1974)
A series of associated encephalocranial and thoracic traumabsms of the Hospital de Clínicas de Montevideo during the last fifteen years ( 1955 to 1969) is revised, The increasing graveness of these lesions -due to the growing mecanization and speed of traffic and industry- is underlined. The causes of death and the physiopathological mecanisms of both traumatic lesions are analyzed, emphasizing their individual noxious effects and their, mutual additive interaction. In the chapter of treatment, reanimation measures including tracheostomy and respiratory assistance in Intensive Care Units, and combined simultaneous emergency ranial and thoracic surgery is discussed.